Deprived neighborhoods and adverse perinatal outcome: a systematic review and meta‐analysis. (13th June 2014) - Vos, Amber A.; Posthumus, Anke G.; Bonsel, Gouke J.; Steegers, Eric A.P.; Denktaş, Semiha
Abstract Objectives This study aims to summarize evidence on the relation between neighborhood deprivation and the risks for preterm birth, small‐for‐gestational age, and stillbirth. Design The design was a systematic review and meta‐analysis. Main outcome measures The main outcome measures included studies that directly compared the risk of living in the most deprived neighborhood quintile with least deprived quintile for at least one perinatal outcome of interest (preterm delivery, small‐for‐gestational age and stillbirth). Methods Study selection was based on a search of Medline, Embase and Web of Science for articles published up to April 2012, reference list screening, and email contact with authors. Data on study characteristics, outcome measures, and quality were extracted by two independent investigators. Random‐effects meta‐analysis was performed to estimate unadjusted and adjusted summary odds ratios with the associated 95% confidence intervals. Results We identified 2863 articles, of which 24 were included in a systematic review. A meta‐analysis (n = 7 studies, including 2 579 032 pregnancies) assessed the risk of adverse perinatal outcomes by comparing the most deprived neighborhood quintile with the least deprived quintile. Compared with the least deprived quintile, odds ratios for adverse perinatal outcomes in the most deprived neighborhood quintile were significantly increased for preterm delivery (odds ratio 1.23, 95% confidence interval 1.18–1.28), small‐for‐gestational age (odds ratio 1.31, 95% confidence interval 1.28–1.34), and stillbirth (odds ratio 1.33, 95% confidence interval 1.21–1.45). Conclusions Living in a deprived neighborhood is associated with preterm birth, small‐for‐gestational age and stillbirth.